Sauter mean diameter statistics of the starch dispersion atomized with hydraulic nozzle - Naz, M.Y. (American Institute of Physics Inc., 2015)
In the reported research work, the microscopic droplet velocity at different axial and radial locations downstream to the nozzle exit was studied by using a non-intrusive Laser Doppler Anemometry (LDA) techniques. These velocity measurements made in the viscous fluid spray sterams were used to predict the different breakup regimes in the flow. It was noticed that the droplet velocity decreased sharply downstream to the nozzle exit, whereas steady decrease in velocity was seen along the radial directions. For shorter injection time periods, the velocity downstream to the nozzle was not following the general breakup model. However, along the radial direction it exactly followed the discussed model. Along the spray centerline, the velocity was decreasing sharply even at far points from the nozzle exit. It was difficult to identify the core region, transition region and fully developed spray region in the flow. It revealed that the jet breakup was not completed yet and further disintegration was taking place along the spray centerline for shorter injection periods below 250 ms. Â© 2015 AIP Publishing LLC.